Zerowaste enterprise / Muhamad Uzair Roslan ... [et al.] - Roslan, Muhamad Uzair; M.Fuad, Muhamad Faiz Afham; Mohammad Shadan, Nadia Farisha Aina; Rosli, Nur Batrisyia; M.Rafi, Muhammad Iqbalhakim
Zero Waste Enterprise will introduce to society out there about the automated drain cleaner as drain cleaning is on of the problems. Malaysian nowadays have and needed adjustments. This drain cleaner driven by a power window motor, voltage rated 12V and current rated <15A. As the unsettled waste production had been increased lately due to the fact that people are full of ego. This can cause the flash flood to occur. As nowadays even in Johor Bahru flash flood always happens as the unmanaged drain around the city with wastes in it blocking the flow of the water thus making the drain stuck